Exploring concepts of definite integrals in two variables using GeoGebra - Pitágoras Pinheiro de Carvalho; Afonso Norberto da Silva; Maria da Cruz Vieira da Silva; William Fernando da Silva Rodrigues (Springer, 2024)
Abstract This work was developed to present constructive steps of multiple integrals using the open-source software Geogebra. The main focus was directed towards creating three-dimensional graphs of integrals through Riemann sums in two variables. Some practical examples are developed to demonstrate the reliability of the presented results, which are compared using traditional algebraic methods and computed in Geogebra. With this, we aim to highlight the potential of Geogebra in teaching integral calculus and make the graphical visualization process less exhaustive.